Traumatic anterior shoulder instability in the athlete - Murray, I. R.; Ahmed, I.; White, N. J.; Robinson, C. M. (Scandinavian Journal of Medicine & Science in Sports, 2013)
Anterior glenohumeral dislocation is common among athletes and may progress to recurrent instability. The pathoanatomy of instability and specific needs of each individual should be considered to prevent unnecessary absence from sport. Traditionally, primary dislocations have been managed with immobilization followed by rehabilitation exercises and a return to sporting activity. However, arthroscopic stabilization and external rotation bracing are increasingly used to prevent recurrent instability. In addition to the typical capsulolabral disruptions seen following a primary dislocation, patients with recurrent instability often have coexistent osseous injury to the humeral head and glenoid. In patients without significant bone loss, open soft-tissue stabilizations have long been considered the `gold standard treatment` for recurrent instability, but with advances in technology, arthroscopic procedures have gained popularity. However, enthusiasm for arthroscopic repair has not been supported with evidence, and there is currently no consensus for treatment. In patients with greater bone loss, soft-tissue stabilization alone is insufficient to treat recurrent instability and open repair or bone augmentation should be considered. We explore the recent advances in epidemiology, classification, pathoanatomy and clinical assessment of young athletes with anterior shoulder instability, and compare the relative merits and outcomes of the different forms of treatment.